Influence of Tiktok Social Media Trend on Fashion Style Among State University of Malang Students - Nadia Jamila; Nadliva Mukammilah Qolbi; Putri Roidatul Mufidah; Rangga Muhammad Hayqal; Sabrina Putri Isnaini; Salsabilah Firdausy Rahmajuwita (Bhinneka Tunggal Ika Journal, 2025)
The Tiktok platform is one of the social media platforms that is able to attract a lot of public attention through various kinds of content. The phenomenon of using Tiktok which is increasingly crowded has an effect on the growing OOTD style trend. Therefore, this study aims to find out how much influence the use of Tiktok social media has on the fashion style of State University of Malang students. The method used in this study is quantitative descriptive with purposive sampling data collection techniques. The instrument used is in the form of a questionnaire that has been determined and arranged properly so as to minimize the opportunity for flexibility and reflexivity. Based on the analysis of the data obtained, it is shown that there is a significance test result (Sig.) with a value of 0.000 which means smaller than the probability or significance criterion (0.05). This shows that there is an influence of the independent variable in the form of the use of the Tiktok application on the fashion style or dress among State University of Malang students.